How Stories Get Made Investigating the Narrative Strategies of 'The Sopranos' - Smith, Anthony (2008)
'The Sopranos' (HBO, 1999-2007), suggests David Thorburn, is ÃÂÃÂ¢ÃÂÃÂÃÂÃÂprobably the most complex narrative in the history of American televisionÃÂÃÂ¢ÃÂÃÂÃÂÃÂ. This is a provocative claim which implies not only that the formal narrative construction of 'The Sopranos' is ÃÂÃÂ¢ÃÂÃÂÃÂÃÂmore complexÃÂÃÂ¢ÃÂÃÂÃÂÃÂ than the narratives of other programmes, but distinct also. But is this the case? Is the 'Sopranos' narrative form ÃÂÃÂ¢ÃÂÃÂÃÂÃÂ a product of the premium cable sector ÃÂÃÂ¢ÃÂÃÂÃÂÃÂ not only distinct from the narratives of network and basic-cable hour-long dramas, but also different from the narratives of other HBO hour-long dramas such as 'Deadwood' (HBO, 2004-2006), 'The Wire' (HBO, 2002-2008) and 'Big Love' (HBO, 2006-)? If this is indeed the case (and this dissertation contends that in some ways it undeniably is), then what is the precise nature of this distinct and complex narrative, and what are the factors within the industrial process of television production which have led to its distinctiveness? This dissertation, by closely examining the narrative strategies utilized by The Sopranos, attempts to address these questions by discovering how Sopranos stories were told and why they were told in this way.